General practitioners' perceptions of their communication with Australian Aboriginal patients with acquired neurogenic communication disorders. Issue 12 (December 2019) - Hersh, Deborah; Armstrong, Elizabeth; McAllister, Meaghan; Ciccone, Natalie; Katzenellenbogen, Judith; Coffin, Juli; Thompson, Sandra; Hayward, Colleen; Flicker, Leon; Woods, Deborah
Highlights: Acquired communication disorders (ACD) in Aboriginal patients challenge GPs. GPs rely on families and Aboriginal Health Workers as interpreters. GPs rarely refer Aboriginal adults to speech pathology for communication. GPs would benefit from more cultural safety and communication training for ACD. Abstract: Objective: Aboriginal people have high rates of stroke and traumatic brain injury (TBI), often with residual, chronic communication deficits and multiple co-morbidities. This study examined general practitioners' (GPs') perceptions of their communication with Aboriginal patients with acquired communication disorders (ACD) after brain injury. Effective communication underpins good care but no previous research has explored this specific context. Methods: A qualitative descriptive approach was employed using interviews and focus groups with 23 GPs from metropolitan Perth and five regional sites in Western Australia. Data were analysed thematically. Results: GPs reported low visibility of Aboriginal patients with ACD in their practices, minimal training on neurogenic ACD, and difficulty distinguishing ACD from cultural-linguistic factors. They had few communication resources, and depended on families and Aboriginal Health Workers to assist in interactions. They rarely used formal interpreting services or referred to speech pathology. They reported communication (dis)ability having low priority in consultations. Conclusion: GPs report difficulty recognising ACD and their lack of prioritising assessment and treatment of communication ability after brain injury potentially compounds the disadvantage and disempowerment experienced by many Aboriginal people. Practice implications: GPs require further communication and cultural training. Improved access to speech pathology and formal interpreting services would be beneficial.